A low-profile planar MIMO array on flexible substrate for mid-band 5G - Hossain, A. K. M. Zakir; Ibrahimy, Muhammad Ibn; Hassim, Nurulhalim; Alam, A. H. M. Zahirul (IEEE, 2024)
Here, a low-profile planar microstrip feed 6 × 6 MIMO array on flexible substrate is designed and realized. This proposed design works with a wideband of 3.75 GHz covering all mid-band 5G frequency ranges from 2.95 GHz to 6.70 GHz. This 6-element MIMO demonstrates a good isolation between the ports with as low as -17.7dB and as high as above -40dB. The combined MIMO far-field radiation patterns yield an ability to radiate almost all directions in both phi = 0 and phi = 90 planes. The realized gain (RG) of the proposed MIMO array achieved is as high as 7.35dBi and never goes below 5dBi in the working band. Whereby, the total efficiency (TE) remains above 90% in the band. The MIMO performance parameters such as Envelop Correlation Coefficient (ECC) and Diversity Gain (DG) values achieving remarkably good as low as 0.001 and close to 10, respectively, exhibiting the quality and robustness of the proposed design. This design will motivate the antenna designer to design a relatively high performing MIMO array on a thin flexible substrate for 5G smartphones..